(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
A prominent topic in contemporary times is the supply and demand for cruelty free products. The information available on product labels should be compasses to guide the consumer at the time of purchase. The objective of the research was to study whether access to information on cosmetic product labels influences the purchasing decision. The methodology adopted exploratory research with a qualitative approach. The research universe was formed by consumers who purchase products in three large wholesale and retail chains in the municipality of Maceió, capital of the state of Alagoas. The sample was random and the data collection instrument used was a Google Forms form. Data collection was carried out from October to December 2023 and involved the participation of 138 participants. The results showed a low percentage of respondents (33.6%) who stated that they read the information on the labels before purchasing the products. 46% of respondents stated that they would prefer to consume products that have the cruelty free seal and 48% stated that they would prefer to consume these products depending on the price charged. The data revealed that, although still timid, there is an uptake of cruelty free products.